2020
DOI: 10.1152/ajpheart.00412.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic nerve transdifferentiation reduces action potential heterogeneity after myocardial infarction

Abstract: Cardiac sympathetic nerves undergo cholinergic transdifferentiation following reperfused myocardial infarction (MI), whereby the sympathetic nerves release both norepinephrine (NE) and acetylcholine (ACh). The functional electrophysiological consequences of post-MI transdifferentiation have never been explored. We performed MI or sham surgery in wild-type (WT) mice and mice in which choline acetyltransferase was deleted from adult noradrenergic neurons [knockout (KO)]. Electrophysiological activity was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…6 B); however, control hearts had faster maximal HRs with SNS compared to DBH-Sap hearts (Control SNS: 442.0 ± 45.1 BPM vs. DBH-Sap: 333.2 ± 62.0 BPM, p < 0.05). We previously showed that SNS in the normal mouse heart leads to APD prolongation and CaTD shortening, while HR is increased 28 . Control hearts responded as expected, with APD prolongation and CaTD shortening at both the base and apex during SNS (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…6 B); however, control hearts had faster maximal HRs with SNS compared to DBH-Sap hearts (Control SNS: 442.0 ± 45.1 BPM vs. DBH-Sap: 333.2 ± 62.0 BPM, p < 0.05). We previously showed that SNS in the normal mouse heart leads to APD prolongation and CaTD shortening, while HR is increased 28 . Control hearts responded as expected, with APD prolongation and CaTD shortening at both the base and apex during SNS (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure 1, since its first use for optical mapping in 2007, blebbistatin has all but replaced the other available EC uncouplers. In fact, in the last three years alone, blebbistatin was used twice as often (1,29,36,41,51,56,59,69,74,76,78,83,85,87) as any other uncoupler for imaging applications (25,27,33,46,54,55,80). The use of BDM/DAM and CytoD for optical mapping has essentially ceased, yet due to its lower cost, BDM/DAM may still be a reasonable choice for larger animal (i.e., non-rodent) studies (10,23,25,35,52,70,77), which require larger amounts of an EC uncoupler (72).…”
Section: Excitation-contraction Uncouplingmentioning
confidence: 99%
“…In contrast, the development of optical mapping offered a new mapping approach with superior spatial resolution (53) that is determined by the image sensor specifications (sensor size, number of pixels, and quantum efficiency) and the optical field of view (9). Additionally, the use of calciumsensitive probes enabled simultaneous measurements of electrical activity and intracellular calcium cycling, as demonstrated by Choi and Salama at the turn of the century (15), and now provides unprecedented insight into ECC parameters in normal and diseased hearts (31,42,56,74,76,83).…”
Section: Introductionmentioning
confidence: 99%
“…In porcine models of chronic ischemia, as well as humans with ischemic cardiomyopathy, histologic changes in stellate ganglia neurons have been observed resulting in inflammation, glial cell activation, and oxidative stress (Ajijola et al, 2012(Ajijola et al, , 2015. Cholinergic transdifferentiation has been described following myocardial infarction, and, in animal models, co-release of acetylcholine with norepinephrine may be antiarrhythmic by reducing actional potential duration dispersion (Olivas et al, 2016;Wang et al, 2020).…”
Section: Cardiac Sympathetic Innervation: In Health and Diseasementioning
confidence: 99%